TLR4 interaction with PIEZO1 facilitates the 5-HT-mediated intestinal motility dysfunction in offspring mice induced by LPS exposure during pregnancy - Ruifang Luo; Yuan Miao; Riqiang Hu; Fang Lin; Junyan Yan; Ting Yang; Lu Xiao; Zhujun Sun; Yuting Wang; Jie Chen (Genes and Diseases)
Several factors during pregnancy, such as changes in serotonin (5-HT) levels, can affect intestinal function in offspring mice. The role of 5-HT in regulating intestinal motility after lipopolysaccharide (LPS) exposure during pregnancy is unclear. In this study, Tlr4fl/fl and Tlr4▵IEC mice were injected with LPS or phosphate-buffered saline during pregnancy to obtain prenatal LPS-exposed or non-exposed offspring mice. Changes in intestinal morphology, motility, and the TLR4 and 5-HT signaling pathways were examined in male offspring mice. The role of TLR4 in regulating 5-HT secretion was investigated in the BON-1 enterochromaffin cell line. In the prenatal LPS-exposed Tlr4fl/fl group, offspring mice exhibited colonic mucosal injury and faster intestinal motility, but these effects were absent when TLR4 was knocked out in intestinal epithelial cells. The TLR4 and 5-HT signaling pathways were activated in the colon of prenatal LPS-exposed Tlr4fl/fl offspring mice but were inactivated in prenatal LPS-exposed Tlr4 knockout offspring mice. In BON-1 cells, TLR4 interacted with the calcium ion channel PIEZO1, causing calcium influx and promoting 5-HT secretion. This process was disrupted by the TLR4 inhibitor TAK242. LPS exposure during pregnancy affected intestinal motility in offspring mice by activating TLR4 pathways in the colon and increasing 5-HT secretion from enterochromaffin cells. The effects of LPS on the intestine might be explained by the interaction between TLR4 and PIEZO1, suggesting that TLR4 is related to abnormal intestinal motility in offspring mice exposed to LPS during pregnancy.